Infrastructuring European migration and border control: The logistics of registration and identification at Moria hotspot. (August 2019) - Pollozek, Silvan; Passoth, Jan Hendrik
This paper examines Moria hotspot in Greece as a logistical site which fulfills two different functions within the European migration and border regime. It locates, contains, and sorts individuals locally at the external borders of the EU and creates, inserts, and processes data for controlling people on the move. Based on ethnographic fieldwork in Greece, including interviews with local administrators from the Registration and Identification Service, Médecins du Monde, Frontex and Hellenic Police and a collection of internal and publicly available planning, policy, and management documents and handbooks, the paper scrutinizes how both the movement of migrants and data is organized at the site. By developing an analytic lens of logistics, it outlines a specific mode of infrastructuring which aligns staff from different organizations with databases, devices, and migrants all in one place and organizes mundane practices such as filling out forms, taking fingerprints, signing, and entering datasets along a chain. That way the hotspot is able to locate, sort, and detain those who arrive at the hardened EU border and to create a data infrastructure for controlling, monitoring, and governing further movement by processing data through the bureaucratic channels of the EU's transnational control assemblages.